KONSTRUKSI SOSIAL PEMBERDAYAAN MASYARAKAT (KASUS PROGRAM ICD RUMAH ZAKAT DI DESA MEKARWANGI KABUPATEN BANDUNG BARAT) - Arini Enar Lestari AR; Munandar Sulaiman; Muhammad Fedryansyah (Department of Sociology Faculty of Social and Political Sciences, 2020)
Social construction is one of the approach in community development. This research aimed to find out the process and results of the social construction of community development through the Integrated Community Development (ICD) Rumah Zakat program in Mekarwangi Village, West Bandung Regency. Mekarwangi Village was one of the target of the ICD program which was considered quite successful in the program implementation by the Rumah Zakat. The social construction of community development in Mekarwangi Village goes through stages of externalization, objectification, and internalization. This stage of social construction was obtained through the results of the dialectical process. This research used qualitative method with a case study approach. Primary data were obtained from informants through observation and in-depth interviews. Secondary data were obtained through relevant literature. These method and approach were used to describe, analyze data and field information that was appropriate with the actual conditions factually and thoroughly about the social construction process of community development through the Integrated Community Development (ICD) Rumah Zakat program in Mekarwangi Village, West Bandung Regency. This was appropriate with the society social construction process proposed by Berger and Luckman (1990). The results of the research shows that dialectics of social construction occurs simultaneously from externalization, objectification until internalization. The externalization process was carried out by preparing a facilitator (RI), making social mapping, formulating an action plan, and reaching the socialization stage. The objectification process was carried out after the community was familiar with the ICD RZ program and starts implementing it. The internalization process was the re-absorption of the program into each community to raise awareness for the importance of the program existence for individuals. ABSTRAK Konstruksi sosial adalah salah satu pendekatan dalam pemberdayaan masyarakat. Penelitian ini bertujuan untuk mengetahui proses dan hasil konstruksi sosial pemberdayaan masyarakat melalui program Integrated Community Development (ICD) Rumah Zakat di Desa Mekarwangi Kabupaten Bandung Barat. Desa Mekarwangi adalah salah satu desa binaan program ICD yang dinilai cukup berhasil dalam pelaksanaan program oleh Rumah Zakat. Konstruksi sosial pemberdayaan masyarakat di Desa Mekarwangi berjalan melalui tahapan eksternalisasi, objektivikasi dan internalisasi. Tahapan konstruksi sosial ini diperoleh melalui hasil proses dialektika. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Data primer diperoleh dari informan melalui observasi dan wawancara mendalam. Data sekunder diperoleh melalui literatur yang relevan. Metode dan pendekatan ini digunakan untuk mendeskripsikan, menganalisis data dan informasi lapangan yang sesuai dengan keadaan sebenarnya secara faktual dan teliti terhadap proses konstruksi sosial pemberdayaan masyarakat melalui program Integrated Community Development (ICD) Rumah Zakat di Desa Mekarwangi Kabupaten Bandung Barat. Hal ini sesuai dengan proses konstruksi sosial masyarakat yang dikemukakan oleh Berger dan Luckman (1990). Hasil penelitian menemukan dialektika konstruksi sosial terjadi secara simultan mulai dari ekternalisasi, objektivikasi sampai internalisasi. Proses eksternalisasi dilakukan dengan mempersiapkan fasilitator (RI), pembuatan social mapping, perumusan action plan, sampai pada tahap sosialisasi. Proses objektifikasi dilakukan setelah masyarakat mengenal program ICD RZ dan mulai melaksanakannya. Proses internalisasi adalah penyerapan kembali program ke dalam diri masing-masing individu masyarakat sehingga menumbuhkan kesadaran terhadap pentinganya keberadaan program bagi diri individu.